2019
DOI: 10.1084/jem.20190293
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenes evades adaptive immunity through specific IgG glycan hydrolysis

Abstract: EndoS from Streptococcus pyogenes hydrolyzes the functionally important glycan on the Fc portion of IgG during infections in humans. In mice with IgG mediated immunity against the M1 protein on the bacteria, EndoS is a virulence factor.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…This fact can be used for early diagnosis of concomitant VGL-6 infection in children with tonsillitis. The study of the properties of Ig G in streptococcal infection is important in terms of the identified opportunities to avoid the pathogen from the immune response [19].…”
Section: Discussionmentioning
confidence: 99%
“…This fact can be used for early diagnosis of concomitant VGL-6 infection in children with tonsillitis. The study of the properties of Ig G in streptococcal infection is important in terms of the identified opportunities to avoid the pathogen from the immune response [19].…”
Section: Discussionmentioning
confidence: 99%
“…showed that the IgG glycan hydrolase from S . pyogenes decreased phagocytic killing of bacteria due to glycan loss and reduction in complement-activation activity, and its expression increased virulence of the organism in a mouse model [ 26 ]. Glycan-dependent complement activation by antibody to PNAG is essential for protective efficacy [ 14 , 17 ], suggesting that antigens inducing neutralizing antibody to the SEE endopeptidase IgeE and the EndoSee glycan hydrolase may need to be included in an effective vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…A strangles vaccine candidate that was recently shown to reduce clinical signs of strangles in a challenge study of ponies contained antigens targeting SEE enzymes that degrade IgG or inhibit its functional activity [25]. Targeting these virulence factors could be essential, as Naegeli et al showed that the IgG glycan hydrolase from S. pyogenes decreased phagocytic killing of bacteria due to glycan loss and reduction in complement-activation activity, and its expression increased virulence of the organism in a mouse model [26]. Glycandependent complement activation by antibody to PNAG is essential for protective efficacy [14,17], suggesting that antigens inducing neutralizing antibody to the SEE endopeptidase IgeE and the EndoSee glycan hydrolase may need to be included in an effective vaccine.…”
Section: Plos Onementioning
confidence: 99%
“…IdeS hydrolyzes four subclasses of IgG, whereas EndoS specifically alters IgG Fc glycosylation [ 68 , 69 ]. Subsequently, altered IgG cannot opsonize the pathogen resulting in impaired phagocytosis and pathogen clearance by phagocytic cells.…”
Section: Major Gas Virulence Factorsmentioning
confidence: 99%